2020
DOI: 10.1111/cogs.12814
|View full text |Cite|
|
Sign up to set email alerts
|

Lossy‐Context Surprisal: An Information‐Theoretic Model of Memory Effects in Sentence Processing

Abstract: A key component of research on human sentence processing is to characterize the processing difficulty associated with the comprehension of words in context. Models that explain and predict this difficulty can be broadly divided into two kinds, expectation‐based and memory‐based. In this work, we present a new model of incremental sentence processing difficulty that unifies and extends key features of both kinds of models. Our model, lossy‐context surprisal, holds that the processing difficulty at a word in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
145
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(152 citation statements)
references
References 127 publications
5
145
0
2
Order By: Relevance
“…At a minimum, our results indicate that the relationship between surprisal and reading times is not linear in extreme conditions such as MV/RR garden path constructions. It is possible that such a non-linear relationship may arise naturally if surprisal is augmented with the noisy channel or lossy context hypotheses Bicknell and Levy, 2010;Gibson et al, 2013;Futrell et al, 2020). However, this possibility cannot explain the qualitatively incorrect reading time predictions we observed in NP/Z constructions.…”
Section: Discussionmentioning
confidence: 79%
“…At a minimum, our results indicate that the relationship between surprisal and reading times is not linear in extreme conditions such as MV/RR garden path constructions. It is possible that such a non-linear relationship may arise naturally if surprisal is augmented with the noisy channel or lossy context hypotheses Bicknell and Levy, 2010;Gibson et al, 2013;Futrell et al, 2020). However, this possibility cannot explain the qualitatively incorrect reading time predictions we observed in NP/Z constructions.…”
Section: Discussionmentioning
confidence: 79%
“…The interaction between past exposure and working memory is an active area of research. Recent extensions to the surprisal metric (Hale, 2001; Levy, 2008) such as the lossy‐context surprisal (Futrell et al, 2019; Futrell & Levy, 2017) have been shown to predict locality as well as the forgetting effects pattern in English and German. Certain models of working memory that can perform differential resource allocation based on prior experience (Daily, Lovett, & Reder, 2001; Lovett, Daily, & Reder, 2000) also hold promise in accounting for the interaction of limited working memory capacity and past exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A better prediction maintenance capability in German allows for longer HD between nouns and verbs in the language. One way to formalize better maintenance is by equating prediction strength with memory activation, such that strong/better prediction of a linguistic unit (e.g., verb) leads to a higher memory activation of that linguistic entity and a weak prediction will lead to lower memory activation (Husain & Vasishth, 2014; Husain et al, 2014; also see Campanelli, Van Dyke, & Marton, 2018; Futrell, Gibson, & Levy, 2019). Alternatively, from a connectionist perspective, the network adapts its weights to the frequent word order pattern of the language, thereby becoming better at handling it.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date no such explanation is available for all of the processing patterns summarized in Section 3.1. See Lewis et al (2006, the last bullet in Box 3), Campanelli, Van Dyke, and Marton (2018), and Futrell, Gibson, and Levy (2020), inter alia .…”
mentioning
confidence: 99%